Indole alkaloids from the roots of Nauclea officinalis and their chemotaxonomic significance - Shan-Ze Yin; Bao-Chan Liu; Guo-Lan Ma; Jiu-Wei Ma; Xi-Yang Lei; Bin-Bao Wang; Rui Li; Shao-Jie Lu; Wei-Min Gao; Pei-Gang Ouyang; Cai-Feng Ding (Biochemical Systematics and Ecology, 2026)

Unraveling the toxicological mechanisms of PFAS in metabolic diseases by network toxicology and molecular docking - Zipeng Qiao; Tao Liu; Xiongfei Hu; Weiwei Ni; Bohan Jiang; Chan Lu (Environmental Pollution, 2026)

Can we predict drug permeability class in intestinal epithelial cells using in situ live-cell ATR-FTIR spectroscopy? - Nikunj D. Patel; Yuchen Lu; Khondaker Miraz Rahman; K.L. Andrew Chan (Analytica Chimica Acta, 2026)

Nonlinear structural reorganisation of corn starch induced by high-pressure processing regulates its thermal, pasting and hydration behaviour - Wen-Chien Lu; Yung-Jia Chan; Ching-Jung Lin; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

An entomopathogen-based small-RNA delivery system promotes the biocontrol efficacy against termites - Chen-Chen Zhao; Hang Lu; Xiao-Long Mao; Long-Long Sun; Fang-Chan He; Zheng-Xun Lv; Qing-Bo Tang; Cheng-Wei Li; Long Liu (Pesticide Biochemistry and Physiology, 2026)

Mineral phase transformation drives molecular fractionation of dissolved organic matter during organic acid-driven weathering of bauxite residue - Chenglong Lu; Songlin Wu; Fang You; Dingyi Yu; Jitraporn Vongsvivut; Annaleise Klein; Lars Thomsen; David Parry; Ting-Shan Chan; Longbin Huang (Chemical Geology, 2026)

CD22+-apoptotic vesicles from cardiac fibroblasts provide endogenous cardioprotection against myocardial ischemia-reperfusion injury - Chan Zhang; Hao Hao; Nan Mu; Yishi Wang; Yin Yue; Lu Yu; Heng Ma (Science China Life Sciences, 2026)

Iridescent chitosan membrane as a colorimetric sensor for visual detection of lipid oxidation - Jilong Lu; Meizhen Xie; Lipin Chen; Qing Song; Siew Yin Chan; Yong-Huan Yun (Chemical Engineering Journal, 2026)

A Dataset of Tropical Cyclones in the Western North Pacific from Chinese Fengyun Geostationary Meteorological Satellite Observations over the Past Two Decades - Xiaoqin Lu; Johnny C. L. Chan; Jie Tang; Hui Yu; Feng Lu; Yue Wang; Ming Ying; Runling Yu; Lan Wei; Longping Hu (Advances in Atmospheric Sciences, 2026)
This paper introduces a comprehensive Tropical Cyclone (TC) dataset based on China’s FengYun (FY) series geostationary satellite observations in the Western North Pacific (WNP), designated as FYSATTY. This innovative dataset integrates high-resolution geostationary meteorological satellite observations with best-track data, providing a unique resource for TC monitoring and analysis in the WNP region. FYSATTY is derived from infrared, water vapor, and visible channel imagery captured by the FY-2 and FY-4 satellites, which is processed using an equal-interval latitude-longitude grid system within a 1500-km radius centered on each TC. The best-track data, sourced from the China Meteorological Administration (CMA), is interpolated into 3-h intervals to ensure temporal consistency with the satellite observations. This dataset consists of 99714 observations for 614 TCs from 2005 to 2024 and will be updated annually. It represents the most comprehensive collection of TC satellite imagery derived from the FY series of geostationary meteorological satellites of the National Satellite Meteorological Center (NSMC). It encompasses a synthesis of infrared, water vapor, and visible channel data from the FY-2 and FY-4 satellite series. The dataset has been meticulously cropped and georeferenced using the CMA best-track data, with fundamental geographic spatial calibration completed. Comparative analysis with analogous elements within other TC geostationary meteorological satellite datasets reveals a high degree of consistency. It is suitable for reanalyzing TC best-track data, assessing climatic characteristics of TC satellite observations, and enhancing forecasting capabilities. This dataset is particularly useful for TC research, forecasting, and machine learning, and is publicly available.

Combined effects of extreme heat and NO2 on liver disease progression of T2DM mice - Zipeng Qiao; Fèlix Faming Wang; Xiangling Feng; Chan Lu (Journal of Hazardous Materials, 2026)

Impact of high-pressure processing on the degradation kinetics and bioactivity of resveratrol - Wen-Chien Lu; Yu-Tsung Cheng; Yung-Jia Chan; Shu-Ju Chen; Yan-Zhen Wu; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Gum arabic modulation of physicochemical properties in heat-gelatinised and alkali-treated cassava starch - Yung-Jia Chan; Wen-Chien Lu; Shu-Ju Chen; Jhih-Ying Ciou; Zong-En Li; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Impact of viaduct noise barriers on traffic-induced air pollution in a real urban environment: A Hong Kong case study - Ying Yang; Bin Lu; Qiusheng Li; Pak Wai Chan (Building and Environment, 2026)

Prenatal 6:2 Cl-PFESA exposure and birth weight: A systematic review and meta-analysis - Xiong-fei Hu; Xiu-hong Yang; Shu Yuan; Tian Chen; Zi-yi Luo; Fèlix Faming Wang; Chan Lu (Journal of Hazardous Materials, 2026)

Enhancing Arabica coffee quality through starter-assisted wet and secondary fermentations: Effects on composition and cupping scores - GiGi Chin-Wen Lim; Yi-Chan Chiang; Chih-Yao Hou; Kai-Min Yang; Lu-Sheng Hsieh; Jhih-Ying Ciou (Food Bioscience, 2026)

Characterization and biological activity of djulis (Chenopodium formosanum) phytosomes and in vivo cosmeceutical applications - Chien-Shan Chiu; Yung-Jia Chan; Min-Hsuan Wu; Bing-Lun Hua; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Bioscience, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Mechanistic insights into high-pressure-induced structural and thermal changes of wheat starch in flour and dough systems - Yung-Jia Chan; Ping-Hsiu Huang; Xiao-Song Huang; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Hydrocolloids, 2026)

Transforming stormwater management from Sponge City to Self-Purifying City - Ling-Wen Lu; Faith Ka Shun Chan; Fang-Fang Zhu; Matthew F. Johnson; Wei-Qiang Chen; Yao-Yang Xu (Journal of Environmental Sciences, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Fast Sweeping Method Based on Equivalent Slowness for Solving the Eikonal Equation - Hong-Yi Jiang; Jian-Xun Yang; Yong-ming Lu; Jun-xin Guo; Hao Zhang; Li-chan Wang (Applied Geophysics, 2026)

Captive breeding and early development of tank-reared lyretail anthias Pseudanthias squamipinnis (Peters, 1855): Assessments of hatching success, larval survival, and ontogeny - Ting-Chan Chou; Ang Lu; Yi-Yang Lin; Cheng-Chieh Wu; Hei-Wan Wong; Ho-Fai Yik; Bo-Kai Liao; Hong-Yi Gong; Yen-Ju Pan (Aquaculture, 2026)

Andrographolide-induced PANoptosis underlies its multiple organ toxicity in mice - Na Lu; Yuan-wen Cai; Qi-hai Cai; Xiu-wen Liang; Nuo Sun; On-kei Chan; Zi-jian Shi; Bo Hu; Xian-hui He; Qing-bing Zha; Dong-yun Ouyang (Toxicology and Applied Pharmacology, 2026)

Effect of oxygen-containing functional groups on selenium removal by the carbonaceous adsorbent from MSW incineration flue gas - Shuaijie Yu; Shuai Li; Hongyun Hu; Linxia Gao; Zhong Lin; Chan Zou; Lu Dong; Yongda Huang; Hong Yao (Fuel, 2026)

Parental stress, indoor environment and outdoor air pollution: A complex nexus and its impacts on childhood pneumonia - Chan Lu; Yao Chen; Wenying Sun; Mengju Lan; Zipeng Qiao (International Journal of Hygiene and Environmental Health, 2026)

Nicotinamide mononucleotide supplement combined with prolonging maturation time improves the quality of oocytes cultured in vitro - Meiyun Lv; Xingrong Lu; Peng Qiu; Lei Wang; Yunchuan Zhang; Yanfei Deng; Deshun Shi; Chan Luo (Animal Reproduction Science, 2025)

Seasonal mercury in an endangered primate from fragmented karst forest: Does behavioral observation advance ecotoxicological risk assessment? - Ran Huang; Haili Chen; Qiuyan Guo; Meijing Lu; Shijun Wu; Dengpan Nong; Chan Li; Yanju Ma; Qihai Zhou (Journal of Hazardous Materials, 2025)

Synthetic, structural and magnetic studies of a fluorinated chloro-bridged Cu(II) dimeric complex, [((C2F5CH2OCH2)2py)CuCl2]2, with unusual non–covalent interactions - Norman Lu; Vinay Belur Lokesh; Ka Long Chan; Gurumallappa Gurumallappa; Pin-Xiang Zeng; Dongge Zheng; Kazuhiro Nawa; Taku J. Sato (Journal of Fluorine Chemistry, 2025)

T7 peptide-modified tanshinone IIA-pretreated exosomes promote blood-spinal cord barrier repair after spinal cord injury - Jie Liu; Ziyan Guo; Chenlin Lu; Peiran Chan; Qian Zhu; Runsen Lu; Ziyan Zhu; Mingming Zheng; Juan Wang; Wu Xiong; Guang Kong; Haijun Li (Chemical Engineering Journal, 2025)

Photoelectrochemical sensor incorporating AgNPs-integrated BiOBr/Ti3C2 layed composites for the efficient detection of bisphenol A detection in water and milk samples - Mingfei Pan; Mengjiao Xie; Lu Han; Chan Lu; Jing Cao; Wenjie Chen; Shuo Wang (Food Chemistry, 2025)

Chemical analysis of mulberry (Morus alba L.) leaves treated with jasmonates on nutrition composition and biological activity - Zhi-Ang Zhang; Jia-Ying Liu; Jia-Le Tian; Marriam Khurshid; Cheng-Hai Yan; Richard Ansah Herman; Lu-Chan Gong; Jun Wang (Food Chemistry, 2025)

High-temperature-induced material softening formed in Ni-W-P-SiC composite coating and its wear reduction mechanism - Yutian JIANG; Wei JIAN; Xihe DU; Jie HE; Ka Chun CHAN; Yuk Lun CHAN; Haibo HUANG; Lu REN (Chemical Engineering Journal, 2025)

Mechanistic insights into the role of hydrocolloids in modulating the rheological properties and flow behavior of alkaline-treated cassava starch - Wen-Chien Lu; Yung-Jia Chan; Zeng-Chin Liang; Zong-En Li; Po-Hsien Li (Carbohydrate Polymers, 2025)

Combination of Large Language Model and Retrieval-augmented Generation for Inference of Traditional Chinese Medicine Prescriptions and Syndrome Differentiations: A Study on Sleeping Disorders - PoYu Huang; ChihNung Wang; ShaoHung Lu; YaChuan Chan; ZhiLiang Chen; WenChen Lin; Jung-Peng Chiu; YungHsin Chen (Journal of Medical and Biological Engineering, 2025)
Propose The objective of this study was to combine a large language model (LLM) with retrieval-augmented generation (RAG) to develop a tool for syndrome type determination and a medical prescription inference model for sleep disorders in a generative artificial-intelligence-based traditional Chinese medicine (TCM) system. The tool uses the disease-formula-syndrome inference framework in TCM to map various combinations of prescription formulas and syndromes. Methods This study selected 6,747 cases of sleep disorders along with their single- and compound-herb formula prescriptions (finished herbal products) to construct the RAG knowledge base. A RAG-based LLM was then employed to generate medical prescription formulas corresponding to syndrome types, as well as for reverse generation and validation. Results The results demonstrate that the RAG-based LLM can determine TCM syndrome types that align closely with clinical reality. Moreover, it can consistently provide comprehensive syndrome mappings for various combinations of prescription formulas. However, limitations were observed in a few instances where only single herbs were identified and compound-herb formulas were either omitted or incorrect, resulting in significantly lower scores. Conclusion The results indicate that the proposed method can enhance learning efficiency in TCM diagnostics and support clinical diagnosis and the RAG-based LLM need to be improved to provide comprehensive responses. Future efforts could focus on expanding the dataset and optimizing the LLM to enhance accuracy and reliability.

Furosemide sodium enhanced AQP3 expression by inhibiting NKCC1 leading to improved vitrification freezing rates of mouse and bovine blastocysts - Chang-Guo Min; Xue-Song Shan; Kai-Yan Zhang; Yu-Chan Wang; Xin Ma; Jun Wang; Jing Zhao; Yi Fang; Hong-Yu Liu; He Ding; Dian Wang; Jing Guo; et al. (Theriogenology, 2025)

Early-life indoor environmental exposures and COVID-19 outcomes in Chinese preschool children: A secondary analysis of a multicenter study - Chan Lu; Jing Ma; Zipeng Qiao; Yichen Yu; Wanxue Xu; Wewei Liu; Faming Wang (Journal of Hazardous Materials, 2025)

Realizing practical use of LiNiO2 cathode in halide-based all-solid-state lithium metal batteries - Hsi Chen; Hao-Wen Liu; Yu-Cheng Lu; Pei-Jane Yu; Cheng-Hung Liao; Chun-Chieh Wang; Ting-Shan Chan; Hwo-Shuenn Sheu; Po-Ya Chang; Jeng-Lung Chen; Shu-Chih Haw; Gung-Chian Yin; et al. (Chemical Engineering Journal, 2025)

Haloalkalitolerant plants drive alkaline mineral weathering and dealkalization of seawater-treated bauxite residue - Chenglong Lu; Songlin Wu; Long Ma; Fang You; Narottam Saha; Hao Bu; Joseph Fernando; David Parry; Lars Thomsen; Ting-Shan Chan; Longbin Huang (Plant and Soil, 2025)
Background Ecological engineering of tailings into soil-like growth media (i.e., technosol) has emerged as a nature-based solution for soilless rehabilitation of alkaline bauxite residue. However, field applications often result in spatial heterogeneity, where uneven amendment leaves behind highly alkaline and saline BR pockets that limit sustainable rehabilitation. It is hypothesized that haloalkalitolerant plants with roots partially grown in the improved niches render their strong tolerance of BR matrix to form extensive roots-mineral interfaces, generate physical and biochemical modification, and irreversibly neutralize the extremely alkaline pH in BR niches. Methods In this study, seawater-treated BR was used to simulate these residual alkaline matrices. Four plant species, including two halophytes, one haloalkalitolerant native acacia and one glycophytic sorghum grass were cultured in a sand-BR compartment system to simulate field heterogeneity. Results Massive roots-BR interfaces were formed. Root activities at the interfaces accelerated the weathering of alkaline minerals and neutralized alkaline pH to circumneutral. Halophytes (Atriplex nummularia and Chloris gayana) were found to be the most effective in weathering and neutralizing BR, due to their higher capacity to exude low-molecular-weight organic acids rich in carboxyl groups in roots-BR interfaces. The LMWOAs facilitated Na⁺-H⁺ exchange with sodalite and disrupted its structure. Conclusion These interactions stimulated the formation of nanosized amorphous Al-Si-Fe minerals on root surfaces. Plant uptake of liberated Na led to Na depletion in the rhizosphere. Therefore, halophytic species should be included in the field application to eliminate substrate heterogeneity of eco-engineering soil formation for soilless BR rehabilitation. Graphical Abstract The root activities of pioneer plants effectively weather alkaline minerals and neutralize alkaline pH in bauxite residue.

Oral g-C3N4-based nanosheets as a universal metal antagonist inhibit cuproptosis pathway for reversing inflammation and injury of Wilson's disease - Xiaoying Xu; Wei Zhao; Lige Qiu; Fei Liu; Yanhong Su; Ligong Lu; Weiguo Xu; Yongjun Peng; Meixiao Zhan; Ke He; Leung Chan (Chemical Engineering Journal, 2025)

Development of an Anatomy-Mimicking, Wave Transport-Preserving Mock Circulation Loop for Evaluating Pulsatile Hemodynamics as Supported by Cardiovascular Assist Devices - Pong-Jeu Lu; Ming-Yao Chan; Steven Tsui; Tzung-Tza Shen; Jui-Chih Chang (Cardiovascular Engineering and Technology, 2025)
Objective Assessing circulatory hemodynamics in-vitro is crucial for cardiovascular device design before in-vivo testing. Current mock circulation loops (MCLs) rely on simplified, lumped-parameter hydraulic representations of human circulation. There is a need for a more sophisticated MCL that can accurately represent the human circulatory physiology and allow for critical assessment of device-supported hemodynamics. Methods An anatomy-mimicking MCL design guided by one-dimensional flow models has been developed, using tree-like arterial casts to create a complex system. The MCL comprises cardiac simulators, systemic circulatory subsystems consisting of 46 connected arterial casts, and lumped venous and pulmonary components. A parameter tuning process was also developed to ensure that the simulated MCL baselines are consistent with targeted healthy or heart failure scenarios. Results Blood pressure and flow waveforms in the thoracic aorta, upper and lower limb arteries and abdominal organs (kidney, liver, spleen, etc.) were reproduced and validated against published data. Complex afferent and efferent flows in cerebral circulation and phasic coronary flow subjected to myocardial compression effect were replicated with precision. Pulse wave behavior was authentically generated and compared favorably to the published in-vivo and in-silico results. Conclusion This wave transport-preserving MCL is able to simulate pulsatile human circulatory hemodynamics with sufficient detail and accuracy. Complex cardiovascular device-intervened hemodynamics in large arteries and end organs can be systematically assessed using this new MCL, potentially contributing to a rapid and accurate in-vitro simulation to help advance device design and functional optimization.

Effects of early-life air pollution exposure on childhood COVID-19 infection and sequelae in China - Chan Lu; Wen Deng; Zipeng Qiao; Wenying Sun; Wanxue Xu; Ting Li; Faming Wang (Journal of Hazardous Materials, 2025)

Size Characteristics of Tropical Cyclones Affecting East China and Those in the Western North Pacific - Xiaoqin Lu; Johnny C. L. Chan; Ming Ying; Hui Yu (Advances in Atmospheric Sciences, 2025)

Low-coverage whole-genome sequencing for differentiating cervical cancer from cervical intraepithelial neoplasia and benign diseases - Tingting Zhang; Fang Gu; Jia yi He; Weihua Li; Ruxue Han; Xinyu Liu; Chan Dai; Zhendong Qin; Di Zhang; Jun Lu; Hua Li (Chromosome Research, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Higher bisphenol analogues exposure levels in e-waste workers and their associations with DNA oxidative damage in Hong Kong - Gengze Liao; Xueqiong Weng; Feng Wang; Yanny Hoi Kuen Yu; Samuel Yeung-shan Wong; Victoria H. Arrandale; Alan Hoi-shou Chan; Shaoyou Lu; Lap Ah Tse (Environmental Research, 2025)

Independent and synergistic effects of extreme heat and NO2 pollution on diabetic nephropathy in a type II diabetes mouse model - Zipeng Qiao; Xiangling Feng; Wenying Sun; Faming Wang; Chan Lu (Environmental Pollution, 2025)

Fine particulate matter components and reproductive hormones in female adults: A 15-year longitudinal cohort study - Siyi Chen; Cui Guo; Chunquan Ou; Yiling Zheng; Yufei Liu; Jun Ma; Xingcheng Lu; Bo Huang; Ta-Chien Chan (International Journal of Hygiene and Environmental Health, 2025)

Monitoring slow-moving deep-seated landslide using PSI technique: a case study of a potential sliding slope from southern Taiwan - Abhishek Lakhote; Yu-Chang Chan; Chiao-Yin Lu; Gopal Kumar; Cheng-Wei Sun (Landslides, 2025)
Studying slow-moving, deep-seated landslides is crucial due to their long-lasting effects on landscapes, infrastructure, and communities. In mountainous regions like Taiwan, understanding these landslides is vital for hazard mitigation and land-use planning. Over 2500 pre-existing landslides have been cataloged in Taiwan using LiDAR data, with many identified as potential slow-moving landslide zones, including a significant site, the Liugui-D047, near Hsinfa Village in southern Taiwan. This study aims to understand the E-W and vertical deformation rates at the potential landslide site using the persistent scattering interferometry (PSI) technique. PSI is particularly effective for detecting slow-moving landslides, providing millimeter-level precision in surface deformation measurements over time. By utilizing open-source tools like ISCE and StaMPS, we conducted a five-year PSI analysis from 2018 to 2023 to monitor surface movements at the site. Our results revealed minimal deformation rates, with westward movements ranging from 4.1 to 2.2 mm/yr and vertical downward movements from 4.2 to 1.4 mm/yr. These findings were validated by in situ measurements collected in 2023, confirming the observations of PSI for long-term monitoring. This highlights the effectiveness of combining PSI techniques with open-source tools for monitoring landslide sites, especially in areas with limited in-situ resources. Our study shows that this integration can yield detailed, long-term insights into surface deformations while reducing the costs of extensive in-situ monitoring. Additionally, our findings indicate that the topographically well-defined Liugui-D047 landslide site remained stable with minimal movement over five years, though ongoing monitoring is essential due to multiple influencing factors.

Eco-friendly utilization and microbiological characteristics of coal gangue substrate via functional microbial fermentation - Junhao Shi; Xiaoyu Zhang; Mengting Lu; Xingxing He; Yong Wan; Xuejing Yu; Zhiyong Huang; Minmin Cai; Chan Yu (Environmental Research, 2025)

High-efficiency flavonoid deglycosylation of whole cells with surface display of α-L-rhamnosidase in Escherichia coli - Cheng-Hai Yan; Ding Wang; Ruo-Xi Mei; Lu Tan; Yi-Jiang-Cheng Li; Richard Ansah Herman; Yan Xu; Lu-Chan Gong; Jun Wang (Food Bioscience, 2025)

Association between air temperature exposure and childhood rhinitis risk, and the mediating role of ambient O3: A multi-city study of 40,103 Chinese preschool children - Zhiping Niu; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Jing Wei; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Parental stress modifies effects of early life exposure to interior environmental factors and extraventricular air pollution on childhood otitis media - Chan Lu; Xianglong Xiao; Wen Deng; Jing Ma; Wenhui Yang; Faming Wang (Building and Environment, 2025)

Eco-morphological traits inform responses of diatom assemblages to urbanization in rivers in China - Xuan Wu; Xinyi Liu; Chan Liu; Lu Tan; Yushun Chen; Tao Tang (Hydrobiologia, 2025)

New perspectives on different Sacha inchi seed oil extractions and its applications in the food and cosmetic industries - Wen-Chien Lu; Chien-Shan Chiu; Yung-Jia Chan; Amanda Tresiliana Mulio; Po-Hsien Li (Critical Reviews in Food Science and Nutrition, 2025)

Exposure to outdoor humid-heat and indoor dampness-mold during infancy is associated with increased childhood asthma risk: A large-scale multi-city study in Chinese preschool children - Zhiping Niu; TianYi Chen; Ling Zhang; Xin Zhang; Chan Lu; Tingting Wang; Xiaohong Zheng; Dan Norback; Juan Wang; Yanyi Xu; Feng Li; Li Peng; et al. (Sustainable Cities and Society, 2025)

Increased health risk from co-exposure to polycyclic aromatic hydrocarbons, phthalates, and per- and polyfluoroalkyl substances: Epidemiological insight from e-waste workers in Hong Kong - Junye Bian; Zhihui Guo; Gengze Liao; Feng Wang; Yanny Hoi Kuen Yu; Victoria H. Arrandale; Alan Hoi-shou Chan; Jiayin Huang; Yiming Ge; Xinjie Li; Xulong Chen; Bingjun Lu; et al. (Science of The Total Environment, 2025)

The long noncoding RNA ALEX1 confers a functional phase state of ARF3 to enhance rice resistance to bacterial pathogens - Meng-Qi Lei; Rui-Rui He; Yan-Fei Zhou; Lu Yang; Zhen-Fei Zhang; Chao Yuan; Wen-Long Zhao; Yu Cheng; Jian-Ping Lian; Yu-Chan Zhang; Wen-Tao Wang; Yang Yu; et al. (Molecular Plant, 2025)

Influence of different hydrocolloids on the pasting, rheological, and morphological characteristics of heat gelatinized cassava starch - Wen-Chien Lu; Yung-Jia Chan; Zong-En Li; Po-Hsien Li (Food Chemistry, 2025)

Chlorate in foodstuffs from south China and its implication for human exposure - Yining Chen; Zhou Zhu; Jiajia Ji; Yiming Ge; Shihua Zhong; Chan Nie; Shaoyou Lu (Food and Chemical Toxicology, 2025)

Parental stress and environmental influences on children's physician-diagnosed food allergy - Chan Lu; Ying Jiang; Lin Wang; Mengju Lan; Faming Wang (Building and Environment, 2025)

Early-life exposure to outdoor temperature and the risk of childhood allergic diseases: A multicentre retrospective cohort study - Faming Wang; Lin Wang; Ying Jiang; Mengju Lan; Wenhui Yang; Zijing Liu; Chan Lu (Building and Environment, 2025)

Bifunctional MOFs Nanozyme with Peroxidase Activity and Stimulus-responsive Fluorescent for Determination of Glyphosate - Yu-Meng Guo; Zi-Chong Chen; Kai-Xiang Zhang; Liu-Lu Liu; Chan Huang; Qing Li (Journal of Fluorescence, 2024)

An enhanced dechlorination method of solid waste incineration fly ash washed by recyclable organic solvent and water mixtures - Peixuan Zhao; Hongyun Hu; Yipeng Wang; Chan Zou; Sihua Xu; Siyi Chen; Huimin Liu; Zhao Zhou; Lu Dong; Hong Yao (Desalination, 2024)

Parental stress interaction with environmental factors in childhood allergic asthma: Early life significance - Chan Lu; Lin Wang; Mengju Lan; Ying Jiang; Faming Wang (Building and Environment, 2024)

Hydrologic Responses to Climate Change and Implications for Reservoirs in the Source Region of the Yangtze River - Pengcheng Qin; Hongmei Xu; Zhihong Xia; Lüliu Liu; Bo Lu; Qiuling Wang; Chan Xiao; Zexuan Xu (International Journal of Climatology, 2024)
Understanding the hydrological impacts of climate change is essential for robust and sustainable water management. This study assessed the hydrologic conditions under changing climate in the Jinshajiang River basin, the source region of the Yangtze River, using the hydrological model SWAT with the historical observations and the future climate simulations under two Shared Socioeconomic Pathways (SSP2‐4.5 and SSP5‐8.5). For the historical period, with an increasing trend of precipitation, evapotranspiration, and snowmelt, streamflow increases in upstream region but keeps decreasing in the downstream catchment. For future scenarios, a warmer and wetter climate is projected for the basin throughout the 21st century, leading to an overall increase in mean and extreme streamflow. The streamflow magnitude increases more significantly in the far future than in the near future, and more significant under SSP5‐8.5 than SSP2‐4.5. The projected remarkable increase in precipitation causes the transition in changing trend of streamflow compared with the historical period. The projected warming leads to a continuing decline in snowfall and snow water equivalent, followed by an earlier snowmelt and higher peak streamflow, especially at the upstream catchment. Ultimately, reservoirs in the basin are expected to gain more inflows, however, with greater variability including higher likelihoods of flood and drought events, which impose potential challenges on reservoir operations. These outcomes indicate the importance of adaptive water resources management in the melting water contributed basin to sustain and enhance its services under global warming.

Early-life ozone exposure and childhood otitis media: Unveiling critical windows of risk - Wenhui Yang; Zipeng Qiao; Qin Li; Xinhua Jia; Yi Liu; Zhi Zeng; Faming Wang; Chan Lu (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Childhood Helicobacter pylori infection: Impacts of environmental exposures and parental stress - Chan Lu; Wen Deng; Zipeng Qiao; Wenying Sun; Wenhui Yang; Zijing Liu; Faming Wang (Journal of Hazardous Materials, 2024)

Numerical investigation of the oxy-fuel combustion in the fluidized bed using macroscopic model supported by CFD-DDPM - Lu Dong; Liang Wang; Huaizhou Wen; Zhong Lin; Zhiyi Yao; Chan Zou; Hongpeng Xu; Hongyun Hu; Hong Yao (Journal of Environmental Chemical Engineering, 2024)

Tuning Mg-Fe-O solid solutions towards optimized exsolution of active sites for thermal catalytic decomposition of methane - Jingxia Qian; Heping Li; Dongping Sun; Wei Shao; Qianwenhao Fan; Longgang Tao; Xianyue Wu; Lan Zhang; Siew Hwa Chan; Jean Marie Basset; Lu Zhou; Wen Liu (Chemical Engineering Journal, 2024)

Improvement of the Diagnostic Method for the Detection of Parasite Eggs Using the Formalin Ethyl Acetate Concentration Technique - Jia-Hung Liou; Te-Ling Lu; Hui-Fen Cheng; Long-Wei Lin; Po-Cheng Kung; Hong-Jing Chuang; Te-Hsiu Lee; Chee-Hong Chan; Te-Jung Lu (Acta Parasitologica, 2024)

Prenatal and postnatal early life exposure to greenness and particulate matter of different size fractions in relation to childhood rhinitis - A multi-center study in China - Liu Yang; Han Chen; Huiyu Gao; Ying Wang; Tianyi Chen; Magnus Svartengren; Dan Norbäck; Jing Wei; Xiaohong Zheng; Ling Zhang; Chan Lu; Wei Yu; et al. (Science of The Total Environment, 2024)

Mulberry (Morus alba L.) leaf powder modified the processing of meat alternatives: Principal component analysis from apparent properties to chemical bonds - Zhi-Ang Zhang; Xiao-Meng Xun; Richard Ansah Herman; Zhan-Peng Zhang; Cheng-Hai Yan; Lu-Chan Gong; Jun Wang (Food Chemistry, 2024)

Estimated daily intake and cumulative risk assessment of organophosphate esters and associations with DNA damage among e-waste workers in Hong Kong - Gengze Liao; Xueqiong Weng; Feng Wang; Yanny Hoi Kuen Yu; Victoria H. Arrandale; Alan Hoi-shou Chan; Shaoyou Lu; Lap Ah Tse (Chemosphere, 2024)

Mitigating flood impacts on road infrastructure and transportation by using multiple information sources - Xiaohui Lu; Faith Ka Shun Chan; Hing Kai Chan; Wei-Qiang Chen (Resources, Conservation and Recycling, 2024)

Children's food allergy: Effects of environmental influences and antibiotic use across critical developmental windows - Chan Lu; Ying Jiang; Mengju Lan; Lin Wang; Wanzhen Zhang; Faming Wang (Journal of Hazardous Materials, 2024)

High humidity and NO2 co-exposure exacerbates allergic asthma by increasing oxidative stress, inflammatory and TRP protein expressions in lung tissue - Chan Lu; Qin Liu; Zipeng Qiao; Xu Yang; Abbas Norouzian Baghani; Faming Wang (Environmental Pollution, 2024)

Silkworm pupae globulin promotes Cordyceps militaris fermentation: Regulation of metabolic pathways enhances cordycepin synthesis and extends the synthesis phase - Yi-Tong Li; Hao-Tian Yao; Ze-Lai Huang; Lu-Chan Gong; Richard A. Herman; Fu-An Wu; Jun Wang (Food Bioscience, 2024)

Greenness and its composition and configuration in association with allergic rhinitis in preschool children - Han Chen; Xia Meng; Yongfu Yu; Jin Sun; Zhiping Niu; Jing Wei; Ling Zhang; Chan Lu; Wei Yu; Tingting Wang; Xiaohong Zheng; Dan Norbäck; et al. (Environmental Research, 2024)

The effects of repeated freezing and thawing on bovine sperm morphometry and function - Chang-Guo Min; Xin Ma; Yu-Chan Wang; Cheng-Kun Zhong; Chong-shan Yuan; Kai-Yan Zhang; Cheng-Lin Zhan; Sheng-Kui Hou; Xin-Hai Wang; Jun Wang; Jing Zhao; Yi Fang; et al. (Cryobiology, 2024)

Early and late onset childhood eczema: Role of preconceptional, pre-natal and post-natal environmental exposures - Chan Lu; Qin Li; Zipeng Qiao; Bin Li; Qin Liu; Faming Wang (Building and Environment, 2024)

Grapefruit essential oil combined with UV-C treatment: A technology to improve the microbial safety of fresh produce - Ningbo Liao; Xinyun Chen; Mengxuan Tang; Peng Tian; Chengwei Liu; Lu Ruan; Hong Pan; Mei Shu; Chan Zhong; Guoping Wu (Innovative Food Science & Emerging Technologies, 2024)

Revolutionizing flexible Electronics: Integrating liquid metal DIW 3D printing by bimolecular interpenetrating network - Yuan Chen; Yun Lu; Dongbin Fan; Jun Li; Chan Kyung Kim; Dengkang Guo; Gaiyun Li (Chemical Engineering Journal, 2024)

Coupling of gene regulation and carrier modification manipulates bacterial biofilms as robust living catalysts - Cheng-Hai Yan; Yu-Fan Zhan; Huan Chen; Richard A. Herman; Yan Xu; Marriam Khurshid; Lu-Chan Gong; Shuai You; Jun Wang (Bioresource Technology, 2024)

Intrauterine and early postnatal exposures to submicron particulate matter and childhood allergic rhinitis: A multicity cross-sectional study in China - Yachen Li; Lifeng Zhu; Jing Wei; Chuansha Wu; Zhuohui Zhao; Dan Norbäck; Xin Zhang; Chan Lu; Wei Yu; Tingting Wang; Xiaohong Zheng; Ling Zhang; et al. (Environmental Research, 2024)

Interaction of life-time and early-life exposure to antibiotics and indoor environmental factors on childhood plant allergy - Chan Lu; Mengju Lan; Lin Wang; Ying Jiang; Bin Li; Faming Wang (Building and Environment, 2024)

Compound flood effects, challenges and solutions: Lessons toward climate-resilient Chinese coastal cities - Faith Ka Shun Chan; Xiaohui Lu; Jianfeng Li; Yangchen Lai; Ming Luo; Yongqin David Chen; Donghai Wang; Nan Li; Wei-Qiang Chen; Yong-Guan Zhu; Hing Kai Chan (Ocean & Coastal Management, 2024)

Significantly alleviated PM2.5 pollution in cold seasons in the Beijing-Tianjin-Hebei and surrounding area: Insights from regional observation - Yangxi Chu; Xiyuan Chi; Jinhong Du; Jingchun Duan; Chak K. Chan; Keding Lu; Lina Yin; Jihua Tan; Jingnan Hu; Fahe Chai (Atmospheric Research, 2024)

The IL-31/TRPV1 pathway mediates allergic asthma exacerbated by DINP dermal exposure in OVA-sensitized Balb/c mice - Qi Peng; Yang Wu; Yan Li; Chan Lu; Runming Yao; Siyuan Hu; Ning Ma; Shaohui Chen; Xu Yang; Ping Ma (Science of The Total Environment, 2024)

Preconceptional, pregnant, and postnatal exposure to outdoor air pollution and indoor environmental factors: Effects on childhood parasitic infections - Chan Lu; Lin Wang; Ying Jiang; Mengju Lan; Faming Wang (Science of The Total Environment, 2024)

Corrigendum to “Effects of intrauterine and post-natal exposure to air pollution on children’s pneumonia: Key roles in different particulate matters exposure during critical time windows” [J. Hazard. Mater. 457 (2023) 131837] - Chan Lu; Wenhui Yang; Faming Wang; Bin Li; Zijing Liu; Hongsen Liao (Journal of Hazardous Materials, 2024)

Assessment of tropospheric ozone simulations in a regional chemical transport model using GEOS-Chem outputs as chemical boundary conditions - Yuqi Zhu; Yiming Liu; Siting Li; Haolin Wang; Xiao Lu; Haichao Wang; Chong Shen; Xiaoyang Chen; Pakwai Chan; Ao Shen; Haofan Wang; Yinbao Jin; et al. (Science of The Total Environment, 2024)

Home environment exposure and sick building syndrome (SBS) symptoms among adults in southern China: Health associations in 2010 and 2019 - Hong Cheng; Dan Norbäck; Huilin Zhang; Liu Yang; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; et al. (Building and Environment, 2024)

Long-distance migration law of radon in overburden of abandoned goaf during coal spontaneous combustion - Zhikang Chan; Bin Zhou; Junfeng Wang; Zhifan Lu; Qifan Yang; Zhiyu Dong; Kaili Dong (Journal of Environmental Radioactivity, 2023)

Velocity distribution and movement of multiple slow-moving landslides characterized by an optimized MTInSAR workflow - Chiao-Yin Lu; Yu-Chang Chan; Jyr-Ching Hu; Chun-Ying Chiu; Chung-Ray Chu; Chia-Han Tseng; Chih-Hsin Chang (Engineering Geology, 2023)

The dual-targeting mechanism of an anti-inflammatory diarylheptanoid from Curcuma zedoaria (Christm.) Roscoe with the capacity for β2-adrenoreceptor agonism and NLRP3 inhibition - Xiufang Chen; Han Zhou; Tao Hou; Jinli Lu; Jun Wang; Liangliang Zhou; Yaopeng Zhao; Yanfang Liu; Jixia Wang; Xinmiao Liang; Chan Chen (Chemico-Biological Interactions, 2023)

The changing pattern of common respiratory viruses among children from 2018 to 2021 in Wuhan, China - Lu Wan; Liangyu Li; Haiyue Zhang; Chan Liu; Ruiyun Li; Xiaojun Wu; Jianjun Chen (Archives of Virology, 2023)
Background Acute respiratory infections in children are a global public health challenge. Owing to the coronavirus disease (COVID-19) pandemic, non-pharmaceutical interventions, including patient isolation, social distancing, hand washing, and mask wearing, have been widely implemented, impacting the transmission of common respiratory viruses. The aim of this study was to clarify the epidemiological features of respiratory viruses in children less than 14 years of age in Wuhan before and after COVID-19. Methods Respiratory specimens were collected from patients aged Results The number of visits and virus detection rate decreased dramatically after February 2020. The respiratory virus detection rate peaked in January and December and decreased dramatically in February and August. The detection rate was lower in 2021 than in 2018 and 2019. Respiratory syncytial virus (RSV) was identified as the leading pathogen in children aged Conclusions This study revealed the epidemiological patterns of common respiratory viruses from 2018 to 2021. The spectrum of pathogens involved in paediatric respiratory infections had partly changed. Non-pharmaceutical interventions resulted in fewer opportunities for the spread of common viruses but also in an “immunity debt” that could have negative consequences when the pandemic is under control in Wuhan.

Particulate organic emissions from incense-burning smoke: Chemical compositions and emission characteristics - Kai Song; Rongzhi Tang; Ang Li; Zichao Wan; Yuan Zhang; Yuanzheng Gong; Daqi Lv; Sihua Lu; Yu Tan; Shuyuan Yan; Shichao Yan; Jingshun Zhang; et al. (Science of The Total Environment, 2023)

Lactate and protein lactylation: the ugly duckling of energy as the sculpture artist of proteins - Linpeng Li; Shanhu Sun; Yi Wu; Jianghuan Lu; Jingcai He; Keshi Chen; Wai-Yee Chan; Xingguo Liu (Science Bulletin, 2023)

Impacts of intrauterine and postnatal exposure to air pollution on preschool children's asthma: A key role in cumulative exposure - Chan Lu; Lin Wang; Hongsen Liao; Bin Li; Qin Liu; Qin Li; Faming Wang (Building and Environment, 2023)

Dampness and mould in Chinese homes and sick building syndrome (SBS) symptoms – Associations with climate, family size, cleaning and ventilation - Bin Zhang; Dan Norbäck; Hong Cheng; Baizhan Li; Yinping Zhang; Zhuohui Zhao; Qihong Deng; Chen Huang; Xu Yang; Chan Lu; Hua Qian; Tingting Wang; et al. (Building and Environment, 2023)

Campus node-based wastewater surveillance enables COVID-19 case localization and confirms lower SARS-CoV-2 burden relative to the surrounding community - Jangwoo Lee; Nicole Acosta; Barbara J. Waddell; Kristine Du; Kevin Xiang; Jennifer Van Doorn; Kashtin Low; Maria A. Bautista; Janine McCalder; Xiaotian Dai; Xuewen Lu; Thierry Chekouo; et al. (Water Research, 2023)

The adsorption mechanism of arsenic in flue gas over the P-doped carbonaceous adsorbent: Experimental and theoretical study - Chan Zou; Shuai Li; Xuanzhou Huan; Hongyun Hu; Lu Dong; Haojie Zhang; Qiqi Dai; Hong Yao (Science of The Total Environment, 2023)

Effects of pre-natal and post-natal exposures to air pollution on onset and recurrence of childhood otitis media - Chan Lu; Qin Li; Zipeng Qiao; Qin Liu; Faming Wang (Journal of Hazardous Materials, 2023)

Effects of intrauterine and postnatal exposure to meteorological factors on childhood pneumonia - Chan Lu; Wenhui Yang; Mengju Lan; Bin Li; Faming Wang (Building and Environment, 2023)

Intrauterine and early postnatal exposure to air pollution associated with childhood allergic rhinitis - Chan Lu; Faming Wang; Zijing Liu; Bin Li; Wenhui Yang; Hongsen Liao (Chemosphere, 2023)

Effects of intrauterine and post-natal exposure to air pollution on children’s pneumonia: Key roles in different particulate matters exposure during critical time windows - Chan Lu; Wenhui Yang; Faming Wang; Bin Li; Zijing Liu; Hongsen Liao (Journal of Hazardous Materials, 2023)

Effect of NO2 exposure on airway inflammation and oxidative stress in asthmatic mice - Chan Lu; Faming Wang; Qin Liu; Miaomiao Deng; Xu Yang; Ping Ma (Journal of Hazardous Materials, 2023)

Microplastics cause reproductive toxicity in male mice through inducing apoptosis of spermatogenic cells via p53 signaling - Chunsheng Lu; Yuehui Liang; Ya Cheng; Chan Peng; Yuanyuan Sun; Kangle Liu; Yingqing Li; Yixia Lou; Xiao Jiang; Aihua Zhang; Jinyi Liu; Jia Cao; et al. (Food and Chemical Toxicology, 2023)

The migration and transformation mechanisms of heavy metals during molten salt cyclic thermal treatment of MSWI fly ash - Yicheng Wang; Lu Dong; Hongyun Hu; Dahai Yan; Sihua Xu; Chan Zou; Yongda Huang; Guangzhao Guo; Hong Yao (Chemical Engineering Journal, 2023)

The role of meteorological parameters on childhood asthma: Identifying critical windows of susceptibility during pregnancy - Chan Lu; Hongsen Liao; Lin Wang; Qin Li; Qin Liu; Faming Wang (Building and Environment, 2023)

Selected global flood preparation and response lessons: implications for more resilient Chinese Cities - F. K. S. Chan; Zilin Wang; Jiannan Chen; Xiaohui Lu; Taiseer Nafea; Burrell Montz; Olalekan Adekola; Alessandro Pezzoli; James Griffiths; Yi Peng; Pengfei Li; Juanle Wang (Natural Hazards, 2023)

Minimal addition of transglutaminase on the preparation and characteristics of tilapia (Oreochromis mossambicus) surimi - Ping-Hsiu Huang; Yu-Tsung Cheng; Yung-Jia Chan; Wen-Chien Lu; Wen-Ching Ko; Hung-Chun Hsieh; Po-Hsien Li (Fisheries Science, 2023)

Paper-based microﬂuidics and tailored gold nanoparticles for visual colorimetric detection of multiplex allergens - Yuxing Yang; Xiaofei Zeng; Chan Fu; Lingxiao Tan; Naidi Yang; Yongxin Liu; Qian Shen; Jifu Wei; Changmin Yu; Chen Lu (Analytica Chimica Acta, 2023)

Intercellular mitochondrial component transfer triggers ischemic cardiac fibrosis - Chan Zhang; Hao Hao; Yishi Wang; Nan Mu; Wenhua Jiang; Zihui Zhang; Yue Yin; Lu Yu; Alex Chia Yu Chang; Heng Ma (Science Bulletin, 2023)

Research on migration and transformation behavior of selenium during the dual-alkali wet flue gas deacidification process in the simulated flue gas - Huasheng Wang; Bing Yuan; Hongyun Hu; Lu Dong; Chan Zou; Guangzhao Guo; Shuang Deng; Songgeng Li; Hong Yao (Fuel, 2023)

Corrigendum to “Association between early life exposure to indoor environmental factors and childhood asthma” [Build. Environ. 226 (2022) 109740] - Chan Lu; Hongsen Liao; Zijing Liu; Wenhui Yang; Qin Liu; Qin Li (Building and Environment, 2023)

Increased risk of respiratory and allergic diseases in preschoolers from building envelope dampness exposure: Repeated cross-sectional surveys in multicity China - Wei Yu; Yan Zhang; Baizhan Li; Yinping Zhang; Chenqiu Du; Zhuohui Zhao; Dan Norback; Jiao Cai; Qihong Deng; Chan Lu; Hua Qian; Xiaohong Zheng; et al. (Building and Environment, 2023)

Gastrointestinal digestion fates of lipids based on pH-stat and Caco-2 cells models: Superior bioavailability of triglyceride monomer derived from silkworm pupae oil - Cheng-Hai Yan; Xiao-Meng Xun; Richard A. Herman; Yu-Fan Zhan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Bioscience, 2023)

Direct 4D printing of gradient structure of ceramics - Lei Wan; Zhengyi Mao; Hui Liu; Youneng Xie; Fucong Lyu; Zhaowenbo Cao; Yunhu He; Jianan Yin; Xiongqi Han; Wai Yan Kannie Chan; Jian Lu (Chemical Engineering Journal, 2023)

Regional comparison on ciguatoxicity, hemolytic activity, and toxin profile of the dinoflagellate Gambierdiscus from Kiribati and Malaysia - Jingyi Zhu; Wai Hin Lee; Ki Chun Yip; Zhen Wu; Jiajun Wu; Chui Pin Leaw; Po Teen Lim; Chung Kuang Lu; Leo Lai Chan (Science of The Total Environment, 2023)

HAI-1 is required for the novel role of FGFBP1 in maintenance of cell morphology and F-actin rearrangement in human keratinocytes - Dajun D. Lu; Nanxi Huang; Sheng-Wen A. Li; Jessica R. Fang; Chih-Hsin Lai; Jehng-Kang Wang; Khee-Siang Chan; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2023)

Interaction of high temperature and NO2 exposure on asthma risk: In vivo experimental evidence of inflammation and oxidative stress - Chan Lu; Qin Liu; Miaomiao Deng; Hongsen Liao; Xu Yang; Ping Ma (Science of The Total Environment, 2023)

Migration and emission characteristics of trace elements in coal-fired power plant under deep peak load regulation - Huasheng Wang; Chan Zou; Hongyun Hu; Guojian Gu; Lu Dong; Yongda Huang; Shuang Deng; Songgeng Li (Science of The Total Environment, 2023)

Understanding the long-term effects of public open space on older adults’ functional ability and mental health - Yuqi Liu; Yingqi Guo; Shiyu Lu; On Fung Chan; Cheryl Hiu Kwan Chui; Hung Chak Ho; Yimeng Song; Wei Cheng; Rebecca Lai Har Chiu; Chris Webster; Terry Yat Sang Lum (Building and Environment, 2023)

Study on the formation mechanism of a radon source during coal spontaneous combustion in a goaf - Zhifan Lu; Bin Zhou; Junfeng Wang; Zhikang Chan; Qifan Yang; Zhiyu Dong; Kaili Dong (Fuel, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Effect of salt penetration and water migration on cooked salted egg yolk gel during storage: Physicochemical properties, structural characteristics and flavor changes - Qiqi Li; Haobo Jin; Xinyue Zhang; Gan Hu; Chan Lei; Haoyang Sun; Long Sheng; Yongguo Jin; Xi Huang; Lizhi Lu; Zhaoxia Cai (Food Chemistry, 2023)

Effect of starch addition on the physicochemical properties, molecular interactions, structures, and in vitro digestibility of the plant-based egg analogues - Zhou Lu; Yi Liu; Yi En Jayne Lee; Andrew Chan; Pin-Rou Lee; Hongshun Yang (Food Chemistry, 2023)

Effects of timing of complementary food introduction on childhood food allergy development: A modified role of ambient air pollution exposure - Chan Lu; Xin Zhang; Qin Liu; Qin Li; Dan Norbäck; Qihong Deng (Building and Environment, 2023)

Forward and reverse logistics for circular economy in construction: A systematic literature review - Lu Ding; Tong Wang; Paul W. Chan (Journal of Cleaner Production, 2023)

Long-term exposure to traffic-related air pollution and temperature increases gynecological cancers - Hongsen Liao; Rachael Gakii Murithi; Chan Lu; Wenhui Yang; Zijing Liu; Lanqin Cao (Building and Environment, 2023)

Mineral weathering of iron ore tailings primed by Acidithiobacillus ferrooxidans and elemental sulfur under contrasting pH conditions - Qing Yi; Songlin Wu; Yunjia Liu; Ting-Shan Chan; Ying-Rui Lu; Narottam Saha; Gordon Southam; Longbin Huang (Science of The Total Environment, 2023)

Combined effect of preconceptional and prenatal exposure to air pollution and temperature on childhood pneumonia: A case-control study - Wenhui Yang; McSherry Brownel Johnson; Hongsen Liao; Zijing Liu; Xiangrong Zheng; Chan Lu (Environmental Research, 2023)

Effects of short-term and long-term exposure to ambient air pollution and temperature on long recovery duration in COVID-19 patients - Zijing Liu; Qi Liang; Hongsen Liao; Wenhui Yang; Chan Lu (Environmental Research, 2023)

Early-life exposure to air pollution associated with food allergy in children: Implications for ‘one allergy’ concept - Xin Zhang; Chan Lu; Yuguo Li; Dan Norbäck; Padmini Murthy; Radim J. Sram; Qihong Deng (Environmental Research, 2023)

Early life exposure to outdoor air pollution and indoor environmental factors on the development of childhood allergy from early symptoms to diseases - Chan Lu; Zijing Liu; Wenhui Yang; Hongsen Liao; Qin Liu; Qin Li; Qihong Deng (Environmental Research, 2023)

Preconceptional, prenatal, and postnatal exposure to home environmental factors and childhood otitis media - Chan Lu; Qin Li; Zijing Liu; Wenhui Yang; Hongsen Liao; Qin Liu (Building and Environment, 2023)

Effects of mold, water damage and window pane condensation on adult rhinitis and asthma partly mediated by different odors - Juan Wang; Yinping Zhang; Baizhan Li; Zhuohui Zhao; Chen Huang; Xin Zhang; Qihong Deng; Chan Lu; Hua Qian; Xu Yang; Yuexia Sun; Dan Norbäck (Building and Environment, 2023)

A novel antibacterial tyroscherin derivative with a natural unprecedented morpholine-2, 3-dione structural unit from the fungus Pseudallescheria boydii - Ruolan Chen; Ziyang Li; Chan Qin; Peijun Lu; Jiaru Lin; Wenxu Zheng; Yahong Xiong; Chunyuan Li (Natural Product Research, 2022)

Individual variation in buffalo somatic cell cloning efficiency is related to glycolytic metabolism - Chan Luo; Zhiqiang Wang; Jinling Wang; Feng Yun; Fenghua Lu; Jiayuan Fu; Qingyou Liu; Deshun Shi (Science China Life Sciences, 2022)

The Critically Endangered Hainan Gibbon (Nomascus hainanus) Population Increases but not at the Maximum Possible Rate - Guioqi Liu; Xueli Lu; Zhao Liu; Zhi Xie; Xuming Qi; Jiang Zhou; Xiaojiang Hong; Yanni Mo; Bosco P. L. Chan; Colin A. Chapman; Zhigang Jiang (International Journal of Primatology, 2022)
With the ongoing global biodiversity crisis in the Anthropocene, it is critical to understand how to save endangered species to “bend the curve” of biodiversity decline. The Hainan gibbon ( Nomascus hainanus ) is a Critically Endangered species that is endemic to Hainan Island. We performed two synchronized total count surveys in Hainan Tropic Rain Forest National Park in November and December of 2020 and 2021 by locating gibbon groups from their morning calls and conducting detailed counts in all potential habitat fragments. We compared our findings with existing data to model the population trend, and analyzed the potential and realized reproductive potentials. We found 5 groups with a total of 33 gibbons in 2020 and 35 in 2021, including 4 and 6 solitary individuals respectively. This is an increase of 169% since 2003, when there were 13 individuals with 2 groups and 2 solitary individuals. Logistic and linear curves fitted the 2003-2021 population census data equally well. Although the population is growing, it has not realized its full reproductive potential (when all adult females give births at 24-month intervals), suggesting that external factors like available habitat, as well as nutritional, physiological, and behavioral factors may be limiting the population. The gibbon’s recovery demonstrates that establishing a nature reserve with regular patrols, banning logging, curbing poaching, and environmental education have been effective. Because the Hainan gibbon population is still extremely small, carefully planned conservation actions, including an ambitious forest restoration program, will be needed to ensure the species’ continued survival.

Large-scale evaluation of aluminum tolerance in maize (Zea mays L.) acessions - Jianzhou Ding; Wei Yang; Xiaoqi Hu; Weina Yan; Wanpeng Hu; Hongjie Li; Chan Liu; Wenzhu He; Yanli Lu; Shibin Gao; Suzhi Zhang (Theoretical and Experimental Plant Physiology, 2022)

TREM-2 mediates dendritic cell–induced NO to suppress Th17 activation and ameliorate chronic kidney diseases - Ching-Cheng Lin; Ti-Yung Chang; Yong-Chen Lu; Yun-Syuan Wu; Wei Huang; Wei-Chi Lo; Guan-Fu Liu; Wei-Chan Hsu; Pamela S. Ohashi; Tak W. Mak; Jong-Ling Fuh; Hui-Chen Chen; et al. (Journal of Molecular Medicine, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A First Insight Into the Heat-Induced Changes in Proteomic Profiles of the Coral Symbiotic Bacterium Endozoicomonas montiporae - Ya-Fan Chan; Chia-Yu Chen; Chih-Ying Lu; Yung-Chi Tu; Kshitij Tandon; Shinya Shikina; Sen-Lin Tang (Frontiers in Marine Science, 2022)
Endozoicomonas , a core bacterial group in corals, may also be a coral symbiont. Endozoicomonas communities often decrease rapidly in corals under heat stress. However, how the bacteria respond to changes in temperature and coral host during heat stress is unknown. Here, we employed the cultivable, dominant species E. montiporae as a working organism to explore how Endozoicomonas responds to heat stress. We designed two experiments to clarify the extent to which E. montiporae is influenced by temperature and coral host. We detected differentially expressed protein (DEP) profiles in this bacterium at 31 and 33°C compared to 25°C by tandem mass tags-based quantitative proteome analysis. Fifty DEPs, including many heat shock proteins, were detected when the temperature changed. The expression of antioxidant defense proteins and key pyruvate synthase proteins decreased, suggesting that E. montiporae were in a physiology of stress at 33°C. Furthermore, some proteins were differentially expressed because of the heat-stress-treated coral lysate specifically, suggesting that not only heat but also heat-induced host factors can affect the protein expression of the bacterium. This study provides an in-depth analysis of how the molecular mechanisms of Endozoicomonas are affected by heat stress and coral host.

Lessons learnt from Typhoons Fitow and In-Fa: implications for improving urban flood resilience in Asian Coastal Cities - Faith Ka Shun Chan; Xinbing Gu; Yunfei Qi; Dimple Thadani; Yongqin David Chen; Xiaohui Lu; Lei Li; James Griffiths; Fangfang Zhu; Jianfeng Li; Wendy Y. Chen (Natural Hazards, 2022)

Study on urban construction land optimization based on geological environment suitability evaluation - Chan Lu; Lei Shi; Xianchao Zhao; Wei Li (Arabian Journal of Geosciences, 2021)

Evaluation and planning of urban geological and ecological environment quality - Chan Lu; Lei Shi; Xianchao Zhao; Wei Li; Quinn Gustavel (Arabian Journal of Geosciences, 2021)

Cathepsin V Mediates the Tazarotene-induced Gene 1-induced Reduction in Invasion in Colorectal Cancer Cells - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Chan-Yen Kuo; Rong-Yaun Shyu; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2020)

Frequency-dependent changes in fractional amplitude of low-frequency oscillations in Alzheimer’s disease: a resting-state fMRI study - Liu Yang; Yan Yan; Yuxia Li; Xiaochen Hu; Jie Lu; Piu Chan; Tianyi Yan; Ying Han (Brain Imaging and Behavior, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Characterization of a major quantitative trait locus on the short arm of chromosome 4B for spike number per unit area in common wheat (Triticum aestivum L.) - Jinghui Li; Shaozhe Wen; Chaofeng Fan; Minghu Zhang; Shuai Tian; Wenjing Kang; Wenxin Zhao; Chan Bi; Qiuyan Wang; Shuang Lu; Weilong Guo; Zhongfu Ni; et al. (Theoretical and Applied Genetics, 2020)

On the Interfacial Flow Over Porous Media Composed of Packed Spheres: Part 1-Identification of the Effective Slip Length - Jin Gang Lu; Seung Chan Cho; Wook Ryol Hwang (Transport in Porous Media, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Efficacy of internet-based integrated intervention on depression and anxiety symptoms in patients with COVID-19 - Ning Wei; Bo-chao Huang; Shao-jia Lu; Jian-bo Hu; Xiao-yi Zhou; Chan-chan Hu; Jing-kai Chen; Jin-wen Huang; Shu-guang Li; Zheng Wang; Dan-dan Wang; Yi Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Comparative study on the Lower Silurian Longmaxi marine shale in the Jiaoshiba shale gas field and the Pengshui area in the southeast Sichuan Basin, China - Lei Chen; Yongchao Lu; Jianqing Li; Xusheng Guo; Shu Jiang; Chan Luo (Geosciences Journal, 2020)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Release characteristics of nitrogen and phosphorus from sediments formed under different supplemental water sources in Xi’an moat, China - Pan Fan; Yi Wang; Wen-Huai Wang; Bao-Hua Chai; Xin-Xin Lu; Jing-Chan Zhao (Environmental Science and Pollution Research, 2019)

Neonatal Dexamethasone Treatment Suppresses Hippocampal Estrogen Receptor α Expression in Adolescent Female Rats - Hui-Fang Chiu; Michael W. Y. Chan; Chiung-Yin Cheng; Jian-Liang Chou; Jora Meng-Ju Lin; Yi-Ling Yang; Kwok-Tung Lu (Molecular Neurobiology, 2019)

Dynamics of nitrogen, phosphorus, and organic pollutant losses from a small watershed in the drinking-water source protection area in Guiyang City of Southern China - Zhen Hong Wang; Xiao Lu Yin; Li Wan; Chan Min Xu; Meng Jiao Zhang (Environmental Science and Pollution Research, 2019)

Impulse Noise Denoising Using Confidence Measure with Non-sequential Process Order for X-Ray Bio-images - Ching-Ta Lu; Jun-Hong Shen; Ling-Ling Wang; Chih-Chan Hsu; Li-Ling Liu (Journal of Medical and Biological Engineering, 2018)

Mechanical and Clinical Evaluation of a Shape Memory Alloy and Conventional Struts in a Flexible Scoliotic Brace - Wing-Yu Chan; Joanne Yip; Kit-Lun Yick; Sun-Pui Ng; Lu Lu; Kenneth Man-Chee Cheung; Kenny Yat-Hong Kwan; Jason Pui-Yin Cheung; Kelvin Wai-Kwok Yeung; Chi-Yung Tse (Annals of Biomedical Engineering, 2018)

Tectonic implications of Mesozoic magmatism to initiation of Cenozoic basin development within the passive South China Sea margin - Hue Anh Mai; Yu Lu Chan; Meng Wan Yeh; Tung Yi Lee (International Journal of Earth Sciences, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The maize CorA/MRS2/MGT-type Mg transporter, ZmMGT10, responses to magnesium deficiency and confers low magnesium tolerance in transgenic Arabidopsis - Hongyou Li; Ning Wang; Jianzhou Ding; Chan Liu; Hanmei Du; Kaifeng Huang; Moju Cao; Yanli Lu; Shibin Gao; Suzhi Zhang (Plant Molecular Biology, 2017)

Optimal scheduling of household appliances for smart home energy management considering demand response - Xinhui Lu; Kaile Zhou; Felix T. S. Chan; Shanlin Yang (Natural Hazards, 2017)

Idiopathic Autism: Cellular and Molecular Phenotypes in Pluripotent Stem Cell-Derived Neurons - Xiaozhuo Liu; Emilie Campanac; Hoi-Hung Cheung; Mark N. Ziats; Lucile Canterel-Thouennon; Margarita Raygada; Vanessa Baxendale; Alan Lap-Yin Pang; Lu Yang; Susan Swedo; Audrey Thurm; Tin-Lap Lee; et al. (Molecular Neurobiology, 2017)

Prior Visual Experience Modulates Learning of Sound Localization Among Blind Individuals - Qian Tao; Chetwyn C. H. Chan; Yue-jia Luo; Jian-jun Li; Kin-hung Ting; Zhong-lin Lu; Susan Whitfield-Gabrieli; Jun Wang; Tatia M. C. Lee (Brain Topography, 2017)

A Meta-Analysis of Working Memory Impairments in Autism Spectrum Disorders - Ya Wang; Yi-bing Zhang; Lu-lu Liu; Ji-fang Cui; Jing Wang; David H. K. Shum; Therese van Amelsvoort; Raymond C. K. Chan (Neuropsychology Review, 2017)

Interaction mechanism of pepsin with a natural inhibitor gastrodin studied by spectroscopic methods and molecular docking - Jie Wang; Calvin Chan; Feng-wen Huang; Jiang-feng Xie; Hong Xu; Ka-wai Ho; Sheng-gang Zheng; Zhang-li Hu; Jun Lu; Zhen-dan He (Medicinal Chemistry Research, 2017)

Lifetime cancer risk assessment for inhalation exposure to di(2-ethylhexyl) phthalate (DEHP) - Yufeng Miao; Runhuai Wang; Chan Lu; Jinping Zhao; Qihong Deng (Environmental Science and Pollution Research, 2017)

The summer distribution of coccolithophores and its relationship to water masses in the East China Sea - Lee-Kuo Kang; Hsing-Ming Lu; Pei-Ting Sung; Ya-Fan Chan; Yun-Chi Lin; Gwo-Ching Gong; Kuo-Ping Chiang (Journal of Oceanography, 2016)

NKCC1 mediates traumatic brain injury-induced hippocampal neurogenesis through CREB phosphorylation and HIF-1α expression - Kwok-Tung Lu; Tai-Chun Huang; Jia-Yi Wang; Ya-Shen You; Jian-Liang Chou; Michael W. Y. Chan; Peter Y. Y. Wo; Tamara G. Amstislavskaya; Maria A. Tikhonova; Yi-Ling Yang (Pflügers Archiv - European Journal of Physiology, 2015)

Mutations of the SLIT2–ROBO2 pathway genes SLIT2 and SRGAP1 confer risk for congenital anomalies of the kidney and urinary tract - Daw-Yang Hwang; Stefan Kohl; Xueping Fan; Asaf Vivante; Stefanie Chan; Gabriel C. Dworschak; Julian Schulz; Albertien M. van Eerde; Alina C. Hilger; Heon Yung Gee; Tracie Pennimpede; Bernhard G. Herrmann; et al. (Human Genetics, 2015)

Direct-Conversion X-Ray Detector with 50-µm High-Gain Pixel Amplifiers for Low-X-Ray-Dose Digital Mammography - Tsung-Ter Kuo; Chien-Ming Wu; Isaac Chan; Hui-Hsin Lu; Sun-Hua Pao (Journal of Medical and Biological Engineering, 2015)

Characterization of the chaperonin GroEL in Mycoplasma gallisepticum - Lei Tan; Meirong Hu; Shengqing Yu; Xin Wang; Feng Lu; Fang Liu; Xusheng Qiu; Cuiping Song; Yingjie Sun; Chan Ding (Archives of Microbiology, 2015)

Bromodeoxyuridine labelling and fluorescence‐activated cell sorting of polyamine‐transforming bacterioplankton in coastal seawater - Xiaozhen Mou; Jisha Jacob; Xinxin Lu; Maria Vila‐Costa; Leong‐Keat Chan; Shalabh Sharma; Yu‐qin Zhang (Environmental Microbiology, 2015)
Summary Polyamines ( PAs ) are a group of nitrogen‐rich dissolved organic nitrogen ( DON ) compounds that are ubiquitously distributed in marine environments. To identify bacteria that are involved in PA transformations, coastal bacterioplankton microcosms were amended with a single PA model compound, i.e. putrescine ( PUT ) or spermidine ( SPD ), or with no addition as controls ( CTRs ). Bromodeoxyuridine ( BrdU ) was added to all the microcosms to label newly synthesized DNAs . Fluorescence‐activated cell sorting ( FACS ) analysis indicated significant increases in numbers of total cells and cells with both high and low levels of BrdU incorporation in the PUT and SPD microcosms, but not in the CTRs . 16 S rDNA pyrotag sequencing of FACS ‐sorted cells indicated that PUT ‐ and SPD ‐transforming bacteria were composed similarly of a diverse group of taxa affiliated with A ctinobacteria , B acteroidetes , F irmicutes and P roteobacteria (especially R oseobacter of its alpha lineage). Broad taxonomic distribution of PA ‐transforming bacteria was also indicated by the abundance and distribution of PA transporter gene homologues in a survey of sequenced marine bacterial genomes. Our results suggest that PAs may be common DON substrates for marine bacterioplankton, in line with the hypothesis that bacterially mediated PA transformation accounts for an important proportion of marine DON flux.

Association between cytokines and methylation of SOCS-1 in serum of patients with ankylosing spondylitis - Ning-Sheng Lai; Jian-Liang Chou; Gary C. W. Chen; Su-Qin Liu; Ming-Chi Lu; Michael W. Y. Chan (Molecular Biology Reports, 2014)

Mouse models of fukutin-related protein mutations show a wide range of disease phenotypes - Anthony Blaeser; Elizabeth Keramaris; Yiumo M. Chan; Susan Sparks; Dale Cowley; Xiao Xiao; Qi Long Lu (Human Genetics, 2013)

Tai Chi practitioners have better postural control and selective attention in stepping down with and without a concurrent auditory response task - Xi Lu; Ka-Chun Siu; Siu N. Fu; Christina W. Y. Hui-Chan; William W. N. Tsang (European Journal of Applied Physiology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

The impact of low-frequency stimulation of subthalamic region on self-generated isometric contraction in patients with Parkinson’s disease - Chiung Chu Chen; Wey Yil Lin; Hsiao Lung Chan; Po Hsun Tu; Shih Tseng Lee; Chin Song Lu; Peter Brown (Experimental Brain Research, 2013)

Significantly differential diffusion of neuropathological aggregates in the brain of transgenic mice carrying N-terminal mutant huntingtin fused with green fluorescent protein - Pei-Hsun Cheng; Chia-Ling Li; Lu-Shiun Her; Yu-Fan Chang; Anthony W. S. Chan; Chuan-Mu Chen; Shang-Hsun Yang (Brain Structure and Function, 2013)

Apoptosis induced by 1,3,6,7-tetrahydroxyxanthone in Hepatocellular carcinoma and proteomic analysis - Wei-ming Fu; Jin-fang Zhang; Hua Wang; Hong-sheng Tan; Wei-mao Wang; Shih-Chi Chen; Xiao Zhu; Tak-ming Chan; Ching-man Tse; Kwong-sak Leung; Gang Lu; Hong-xi Xu; et al. (Apoptosis, 2012)

Detection and identification of a new phytoplasma associated with periwinkle leaf yellowing disease in Taiwan - Wuu-Yang Chen; Yao-Chen Huang; Meng-Lu Tsai; Chan-Pin Lin (Australasian Plant Pathology, 2011)

Mitochondrial proteomics analysis of tumorigenic and metastatic breast cancer markers - Yi-Wen Chen; Hsiu-Chuan Chou; Ping-Chiang Lyu; Hsien-Sheng Yin; Fang-Liang Huang; Wun-Shaing Wayne Chang; Chiao-Yuan Fan; I-Fan Tu; Tzu-Chia Lai; Szu-Ting Lin; Ying-Chieh Lu; Chieh-Lin Wu; et al. (Functional & Integrative Genomics, 2011)

Microarray Profile of Brain Aging-Related Genes in the Frontal Cortex of SAMP8 - Shao-Chun Chen; Gang Lu; Chu-Yan Chan; Yangchao Chen; Hua Wang; David Tai-Wai Yew; Zhong-Tang Feng; Hsiang-Fu Kung (Journal of Molecular Neuroscience, 2010)

The effect of triptolide on CD4+ and CD8+ cells in the Peyer's patch of DA rats with collagen induced arthritis - Cheng Xiao; Linhua Zhao; Zhenli Liu; Cheng Lu; Ning Zhao; Dajian Yang; Shilin Chen; Johnny Cheuk-on Tang; Albert Chan; Ai-ping Lu (Natural Product Research, 2009)

Wintertime high‐resolution features of sea surface temperature and chlorophyll‐ a fields associated with oceanic fronts in the southern East China Sea - Y. Chang; M.‐A. Lee; T. Shimada; F. Sakaida; H. Kawamura; J.‐W. Chan; H.‐J. Lu (International Journal of Remote Sensing, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

A Novel Oscillating Bioreactor BelloCell: Implications for Insect Cell Culture and Recombinant Protein Production - Jen-Te Lu; Yao-Chi Chung; Zun-Ren Chan; Yu-Chen Hu (Biotechnology Letters, 2005)

Detecting Epstein-Barr virus DNA from peripheral blood mononuclear cells in adult patients with systemic lupus erythematosus in Taiwan - Shan-Fu Yu; Huei-Chuin Wu; Wen-Chan Tsai; Jeng-Hsien Yen; Wen Chiang; Chung-Yee Yuo; Sheng-Nan Lu; Lien-Chai Chiang; Chung-Jen Chen (Medical Microbiology and Immunology, 2005)

The mechanism of honokiol-induced and magnolol-induced inhibition on muscle contraction and Ca 2+ mobilization in rat uterus - Yu-Cheng Lu; Hwei-Hsien Chen; Chien-Hsin Ko; Yi-Ruu Lin; Ming-Huan Chan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Agrobacterium tumefaciens-mediated transformation of an Oncidium orchid - C.-H. Liau; S.-J. You; V. Prasad; H.-H. Hsiao; J.-C. Lu; N.-S. Yang; M.-T. Chan (Plant Cell Reports, 2003)

The Sweet Pepper Ferredoxin-Like Protein (pflp) Conferred Resistance Against Soft Rot Disease in Oncidium Orchid - Chia-Hui Liau; Jian-Cheng Lu; Venkatesh Prasad; Hsin-hao Hsiao; Su-Juan You; Jent-turn Lee; Ning-Sun Yang; Hsiang-En Huang; Teng-Yung Feng; Wen-Huei Chen; Ming-Tsair Chan (Transgenic Research, 2003)

Sweet pepper ferredoxin-like protein (pflp) gene as a novel selection marker for orchid transformation - Su-Juan You; Chia-Hui Liau; Hsiang-En Huang; Teng-Yung Feng; Venkatesh Prasad; Hsin-hao Hsiao; Jian-Cheng Lu; Ming-Tsair Chan (Planta, 2003)

Outbreaks of an iridovirus in red drum, Sciaenops ocellata (L.), cultured in southern China - S P Weng; Y Q Wang; J G He; M Deng; L Lu; H J Guan; Y J Liu; S‐M Chan (Journal of Fish Diseases, 2002)

Associations between the western North Pacific monsoon and the South China Sea monsoon - Lu Riyu; Chan-Su Ryu; Buwen Dong (Advances in Atmospheric Sciences, 2002)

Toxicity of ifosfamide and its metabolite chloroacetaldehyde in cultured renal tubule cells - James Springate; Kenneth Chan; Hong Lu; Sherry Davies; Mary Taub (In Vitro Cellular & Developmental Biology - Animal, 1999)